Exploring the relational qualities of older people in a residential care facility - Du Plessis, Erika (My University, 2013)
The social environment has been recognised as one of the key aspects in determining the quality of life throughout the human lifespan. Human behaviour, thoughts, feelings and attitudes are socially constructed and can only be understood when viewed from the perspective of social interaction. Older individuals, who live in residential facilities experience a diminished quality of life due to factors such as loss of independence, reduced social networks, functional dependence, and contextual changes. Depression, loneliness and social isolation are an integral part of these individuals' lives. People develop specific styles of relating, also referred to as interpersonal styles. The systems theory is used to explain the circular processes of the interaction between people. In particular the Self-Interactional Group Theory (SIGT) is proposed as theoretical framework to explore the relational qualities of older people in a residential care facility. SIGT views the interaction between people on three levels, namely the intra-personal level, the interpersonal level and the group level, which operate interdependently in the interaction between people. The interpersonal level of analysis consists of the definition of the relationship, relational qualities, motivation to engage with people to address needs and needs satisfaction as well as the circular processes of which the interaction consists of. The interactions between people always take place in an interpersonal context, embedded in broader environments. A qualitative and exploratory research design was selected to explore the relational qualities in interactions between older individuals living in a residential care facility. This study is based on data collected during a primary research study at a residential care facility for older individuals in 2013. The purpose of study was to explore the quality of life of older individuals residing in a residential care facility in Gauteng, South Africa. The data-gathering process in the primary research study involved the Mmogo-Method, a visual projective data-gathering method, the World Café method and person-centred interviews to gain insight into the participants' life experiences at the residential care facility. For the purpose of this research, only the person-centred interviews were used for the secondary analysis of the data. Twelve purposely-selected individuals (aged 80 to 95; 3 men and 9 women) from the residential care facility participated voluntarily in the person-centered interviews, which were audio recorded. The collected data were transcribed verbatim and subjected to two different methods of analyses. First, data were analysed thematically by adopting an inductive approach. The themes identified in this first phase were next subjected to a deductive content analysis. The themes were categorised according to the relational variables in accordance with the Interactional Pattern Analysis (IPA), thereby contributing to the trustworthiness of the findings. The findings revealed that the interactions between older individuals take place in a broader environment that advocate the active participation of people. Active participation takes place both in and outside the facility and older people reported that this contributed to their quality of life. The relational qualities that could be described as enhancing interpersonal connectivity and satisfying older people's needs for confirmation were identified as empathy, unconditional acceptance of others, confirmation and interpersonal flexibility. This research, however, highlighted relational qualities that restrained quality of life of older people, namely confusing self-presentation, ineffective expression on needs and withdrawal due to physical immobility. Needs were expressed in a very unspecific, blaming or manipulative manner, and consequently needs were not satisfied, but provoked, instead, feelings of frustration, pain and guilt. This research highlighted the predicament that older people find themselves in. Their decreased physical abilities and limited emotional repertoire to move towards others and the environment also limit their needs satisfaction. The presenting problem of social isolation can be explained by the combination of limited physical mobility and relational qualities that restrain quality of life for older people. This research study thus holds important implications for relationship-focused approaches in residential facilities for older individuals in order to empower and enable them to enhance their quality of life. Specific recommendations include interventions to assist older people to express their needs more effectively and to use opportunities in interaction to confirm them as autonomous functioning older people.
MA (Psychology), North-West University, Potchefstroom Campus, 2014
Keywords: Interactional Pattern Analysis (IPA); Interpersonal relationships; Interpersonal styles; Quality of life; Relational qualities; Residential care facilities; Self-Intergenerational Group Theory (SIGT); Social context; Interaksiepatroonanalise (IPA); Interpersoonlike verhoudings; Interpersoonlike style; Lewenskwaliteit; Residentiële sorg fasiliteite; Self-intergenerasiegroepsteorie (SIGT); Sosiale konteks; Verhoudingskenmerke